2011
DOI: 10.1109/tit.2011.2162190
|View full text |Cite
|
Sign up to set email alerts
|

On the Capacity Achieving Covariance Matrix for Frequency Selective MIMO Channels Using the Asymptotic Approach

Abstract: Abstract-In this contribution, an algorithm for evaluating the capacity-achieving input covariance matrices for frequency selective Rayleigh MIMO channels is proposed. In contrast with the flat fading Rayleigh case, no closed-form expressions for the eigenvectors of the optimum input covariance matrix are available. Classically, both the eigenvectors and eigenvalues are computed numerically and the corresponding optimization algorithms remain computationally very demanding. In this paper, it is proposed to opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 16 publications
(56 reference statements)
2
51
0
Order By: Relevance
“…In [16] the authors generalized this analysis in the context of the multiple access jointly correlated Rician MIMO channels. Interestingly, the mutual information provided by the optimization of the approximation appears numerically to be quite close from the true optimum mutual information, even for realistic values of r and t. These observations were confirmed by the theoretical results of [11,12], which showed that the relative error is a O 1 t 2 term. In this paper, we give a comprehensive introduction to the optimization of large system approximations of average mutual information of MIMO channels.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…In [16] the authors generalized this analysis in the context of the multiple access jointly correlated Rician MIMO channels. Interestingly, the mutual information provided by the optimization of the approximation appears numerically to be quite close from the true optimum mutual information, even for realistic values of r and t. These observations were confirmed by the theoretical results of [11,12], which showed that the relative error is a O 1 t 2 term. In this paper, we give a comprehensive introduction to the optimization of large system approximations of average mutual information of MIMO channels.…”
Section: Introductionsupporting
confidence: 66%
“…In this paper, we give a comprehensive introduction to the optimization of large system approximations of average mutual information of MIMO channels. We note that the main results of this paper were already presented in [11,12]. However, the focus of [11,12] is on the detailed derivation of the large system approximations, while the present paper concentrates on their optimization.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations